Hygienic evaluation of the most common methods of agricultural crops treatment with chemical protection products (literature review) - Borysenko , А.А.; Antonenko, А.М.; Shpak, B.I.; Omelchuk, S.Т.; Bardov, V.G. (Medicni Perspektivi, 2021)
Global strategies, including application of chemical plant protection products, are important in the cultivation of safe corps and preservation of human health. A promising area of preventive medicine, agronomy, agroecology and agroengineering is the optimization of methods of pesticide formulations application. The aim of the work was a hygienic assessment of the most common and latest methods of crops treatment with chemical pesticides. Results. The biological effectiveness of different types of pesticides is achieved by different application rates of the working solution. The most common method of pesticide application is spraying, which ensures the application of pesticides in the drop-liquid state and is characterized by low consumption of active substance per unit area, variable-controlled distribution on the treatment surface, provides good adhesion and retention on facilities, allows the use of combined formulations. One of the most effective ways to minimize the negative impact of chemical plant protection products and achieve economic success is a rational approach to the choice of pesticide application, as it takes into account the hazard class of pesticides, the presence of water protection zones, the sensitivity of target crops, etc. Conclusion. Rational application of pesticides includes minimizing the overall effect of pesticides on human health and the environment and achieving high-targeted biological efficiency. Adherence to the methodology of choosing the type of pesticide application and selection of the type of spray is a key point in optimizing the rational use of chemical plant protection products, which requires a detailed study from the standpoint of both efficiency and safety. Control over compliance with the recommendations should be included in sanitary-hygienic and sanitary-ecological monitoring.